If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 119 = (9 + -5) * T + 67 Combine like terms: 9 + -5 = 4 119 = (4) * T + 67 Reorder the terms: 119 = 67 + 4T Solving 119 = 67 + 4T Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-4T' to each side of the equation. 119 + -4T = 67 + 4T + -4T Combine like terms: 4T + -4T = 0 119 + -4T = 67 + 0 119 + -4T = 67 Add '-119' to each side of the equation. 119 + -119 + -4T = 67 + -119 Combine like terms: 119 + -119 = 0 0 + -4T = 67 + -119 -4T = 67 + -119 Combine like terms: 67 + -119 = -52 -4T = -52 Divide each side by '-4'. T = 13 Simplifying T = 13
| 32-2x=12-20x+4x | | 3(4-2x)=1x+5(1x-2) | | 2n^2+9n-126=0 | | 18x-10=8x+70 | | 80y+16=4y^2+100 | | 4(2x+4y)+5(6x-7y)= | | 5(3-x)=4(1x-3) | | 5n+6=4n+51 | | 10x+7(300-x)=2640 | | -x(x-2)=0 | | 2x+4y+7x-y= | | 0=y^2-20y+21 | | 4x+9=5x-7 | | 2-8cos^2x=0 | | 16-3x=3(2-1x) | | (x-3)(-1+x)=0 | | 13/2=x/52 | | 9-6(4)=-4(4-2*4) | | 42=7x+7 | | 3c*4b= | | 10=5(1x-7) | | 4.8x-52=3.2x-20 | | 2x^2+ln(x^2)=0 | | 2(3x+2y)+3(3x+3y)= | | 2a+3b-a-5b= | | 4-1x=2(2-1x) | | 5(X-4)=2(X+8) | | 9-6x=-4(4-2x) | | 0.55[f-32]=25 | | (7x+5)=0 | | 24x^4+16x^2-8=0 | | sqrt64/25 |